Acromio-Humeral Distance Is Associated with Shoulder External Strength in National Elite Badminton Players-A Preliminary Study - Simon Vadstrup Schmidt; Jannik Andersen Engelhardt; Ann Cools; Stig Peter Magnusson; Christian Couppé (MDPI AG, 2021)
Purpose: To examine acromio-humeral distance (AHD) and shoulder isometric strength for external rotation (ER) and internal rotation (IR) in national elite badminton players. Methods: Seven elite badminton players with asymptomatic shoulders aged 24 ± 4 (mean ± SD) from the Danish national badminton team were investigated. Shoulder AHD, isometric strength in ER and IR were bilaterally assessed with ultrasonography and a hand-held dynamometer (HHD). Results: AHD was greater on the dominant vs. the nondominant side (p = 0.018). Moreover, IR strength was greater on the dominant side vs. the nondominant side (p = 0.041). Furthermore, AHD and ER strength were highly correlated on the dominant side (p = 0.007, r = 0.900). A correlation was also shown between AHD and the ER/IR strength ratio on the dominant side (p = 0.033, r = 0.793). Conclusion: This preliminary study demonstrates that shoulder ER strength is strongly associated with AHD size, largely reflecting supraspinatus tendon-muscle hypertrophy as a result of sport-specific adaptation in national elite badminton players with asymptomatic shoulders. These novel data also suggest that habitual loading of the shoulder improves the supraspinatus tendon size, which may lower the mechanical stress and potentially reduce the risk of injury. This warrants strengthening the shoulder external rotators as a potential strategy to reduce the risk of future shoulder injury.